A multiagent socio-hydrologic framework for integrated green infrastructures and water resource management at various spatial scales - M. Zhang; T. F. M. Chui (Hydrology and Earth System Sciences, 2025)
Green infrastructures have been widely used to manage urban stormwater, especially in water-stressed regions. They also pose new challenges to urban and watershed water resources management. This paper focuses on the green-infrastructure-induced dynamics of water sharing in a watershed from three spatial scales. A multiagent socio-hydrologic model framework is developed to provide an optimization-simulation method for city-, inter-city- and watershed-scale, termed Integrated GIs and Water Resources Management (IGWM), that comprehensively considers the watershed circumstances, the urban water managers, and the watershed manager–urban water manager interactions. We apply the framework to conduct three simulating experiments in the Upper Mississippi River basin, USA. Four patterns in city-scale IGWM are classified, and two dynamics of cost and equity in inter-city- and watershed-scale IGWM are characterized through various sensitivity, scenario, and comparative analyses. The modeling results could advance our understanding of the role of green infrastructures and the impact of water policy in urban and watershed water resources management and assist water managers in making associated decisions.